The Psychometric Properties of the Personality Inventory for the DSM-5 (PID-5) in a colombian clinic sample (2019)
ABSTRACT: to validate the Personality Inventory for DSM-5 (PID-5) in a Colombian clinical population and the gender differences. Participants: 341 patients between 18 and 60 years of age, 60% of women. Method: Confirmatory Factor Analyses (AFC) and concurrent validity whit PBQ-SF. Results: supported the existence of the 25 first-order factors. In terms of domains (second-order analysis), several organization models were posed. The results supported the model proposed by Krueger, Derringer, Markon, Watson, and Skodol (2012): χ2(2661, n = 341) = 3350, RMSEA = 0.028 (90% CI: 0.025; 0.030), CFI = 0.99, NNFI=0.99. Men scored significantly higher than women on grandiosity, irresponsibility, manipulativeness, risk-taking, antagonism, and disinhibition. Women scored significantly higher than men on emotional lability and intimacy avoidance. The concurrent validity of PID with the PBQ-SF was high, giving support to the traits of personality disorder models of the DSM-5.